2023
DOI: 10.1097/coc.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Negative Lymph Node Count in Resected Stage I–IIIa Small-cell Lung Cancer

Abstract: Objectives: The prognostic significance of the negative lymph node (NLN) count has been confirmed in various cancers but not in small-cell lung cancer (SCLC). We aimed to evaluate the correlation between the NLN count and the prognosis of patients with stages I–IIIa SCLC who underwent lobectomy. Methods: Data on the clinical characteristics of SCLC patients who underwent lobectomy between 2000 and 2019 were collected from the SEER database and organized based on the X-tile plots to identify the optimal cutof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the Surveillance, Epidemiology, and End Results (SEER) Survey from 2010 to 2015, among the age, race, sex, stage, primary site, histologic type, chemotherapy and radiation parameters, only age, stage, and chemotherapy have been reported to be associated with survival in patients with resected SCLC [5]. Sex [55], visceral pleural invasion [56], lymphocyte-tomonocyte ratio [57], adjuvant chemotherapy after surgical resection [58], TNM stage and tumor location [59], and negative lymph node (NLN) [60] are among other factors reported to be associated with OS in patients who underwent surgical resection. In this study, sex and UICC stage were found to be associated with overall survival in the EGAD00001001244 and GSE60052 cohorts, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the Surveillance, Epidemiology, and End Results (SEER) Survey from 2010 to 2015, among the age, race, sex, stage, primary site, histologic type, chemotherapy and radiation parameters, only age, stage, and chemotherapy have been reported to be associated with survival in patients with resected SCLC [5]. Sex [55], visceral pleural invasion [56], lymphocyte-tomonocyte ratio [57], adjuvant chemotherapy after surgical resection [58], TNM stage and tumor location [59], and negative lymph node (NLN) [60] are among other factors reported to be associated with OS in patients who underwent surgical resection. In this study, sex and UICC stage were found to be associated with overall survival in the EGAD00001001244 and GSE60052 cohorts, respectively.…”
Section: Discussionmentioning
confidence: 99%